2019
DOI: 10.1177/0300060519893852
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA-DRB1* allele polymorphism and caries susceptibility in Han Chinese children and adolescents in the Xinjiang Uygur Autonomous Region

Abstract: Objective The rate of caries and the mean number of decayed, missing, or filled teeth were reported to be significantly higher in children in the Xinjiang Uygur Autonomous Region than in children in eastern China. Little is known regarding the genetic basis of caries among residents of the Xinjiang Uygur Autonomous Region. This study investigated the association between HLA-DRB1 alleles and caries susceptibility in Han Chinese children and adolescents in the Xinjiang Uygur Autonomous Region. Methods HLA-DRB1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…This difference can be attributed to the difference in age group, as this study was conducted among children, in addition to the difference in race studied [ 28 ]. Moreover, the results of this study differed from Wang et al study found that HLA-DRB1*13 allele frequency was significantly higher in patients with caries while HLA-DRB1*09 allele was significantly lower in patients with caries than in healthy controls [ 29 ]. This difference can be attributed to the difference in the studied community.…”
Section: Discussioncontrasting
confidence: 96%
“…This difference can be attributed to the difference in age group, as this study was conducted among children, in addition to the difference in race studied [ 28 ]. Moreover, the results of this study differed from Wang et al study found that HLA-DRB1*13 allele frequency was significantly higher in patients with caries while HLA-DRB1*09 allele was significantly lower in patients with caries than in healthy controls [ 29 ]. This difference can be attributed to the difference in the studied community.…”
Section: Discussioncontrasting
confidence: 96%